Konstruksi Maqasid Syariah dan Sosiologi Hukum Islam pada Aktualisasi Day Care Lansia di Era Modern - Mursidah, Ida; Humaeroh, Humaeroh; Zulfikar, Faisal (Family Law Study Program, Faculty of Sharia and Law, UIN Sunan Gunung Djati Bandung, 2025)
Day care for the elderly has become a new trend in the modern era in providing services in terms of psychological, sociological, motor and religious recovery for the elderly. The purpose of this study is to analyze the role and function of elderly day care, to describe the construction of Maqasid Syariah and the Sociology of Islamic Law on the actualization of day care for the elderly in the modern era. The author's ethnographic qualitative research method was used to obtain authentic data from the elderly and elderly day care managers as primary data. The results of this study are that the role and function of day care for the elderly provides services for mental and spiritual strengthening (tafaqquh fi al din) and Islamic values (Islamic Values) through the realization of the programs provided, while the construction of sharia maqosid in day care for the elderly can realize the stages of daruriyyat, hajjiyat, and tahsiniyat through Ahamiyyatus al syari'iyyah, namely maintaining religion, maintaining reason, and taking care of offspring, To protect the soul, and to protect the treasures. The sociological construction of Islamic Law in the actualization of day care for the elderly in the modern era is based on several studies, namely, in the values of Islamic Law there is noexplicit prohibition on day care for the elderly. The social practices carried out by day care for the elderly through their services provide goodness for the elderly psychologically, sociologically, motorly, religiously. Legal policy according to Law No. 13 of 1998 concerning Social Welfare for the Elderly, that the Indonesian government has provided clear regulations related to the implementation of day care for the elderly through the Decree of the Minister of Social Affairs of the Republic of Indonesia Number 76/HUK/2011 concerning the Determination of Institutions/Foundations Recipients of Assistance for the Implementation of the Elderly Daily Service Program.